Management Of Multidiciplinary Aesthetic Treatment In Rotation And Crossbite Tooth With Avulsion Due To Trauma Injuries - Nanik Zubaidah; Nadira Nurin Febrianti; Ivan Nur Fadela; Cindy Ramadhan Putri; Muhammad Dimas Aditya Ari Ari; Nirawati Pribadi; Sri Kunarti (Universitas Airlangga, 2021)
Background: Anterior teeth that experience rotation and crossbite also lose avulsed teeth due to trauma but can be treated with endo restoration treatment. Loss of anterior teeth due to trauma can impact the appearance and decrease self-confidence due to aesthetic factors and phonetic disorders. Objective: to provide information about the management of anterior teeth that undergo rotation and crossbite accompanied by avulsion due to traumatic injury by correcting the position of the teeth through a multidisciplinary approach. Case Report: A 21-year-old woman with 12 teeth had distobuccal rotation and 22 crossbite, while her front teeth 11 and 21 were avulsed due to trauma from falling from a motorcycle. Patients feel embarrassed and lack confidence when laughing and experience phonetic disturbances when speaking. According to the stomatognathic system, the patient comes to the clinic to treat his front teeth to restore their shape, esthetics, and function. Case management: Endo restoration treatment was carried out on 12 rotated teeth and 22 crossbites through root canal treatment, insertion of posts, and cores which will be used as abutments in the manufacture of fixed-fixed bridges avulsed teeth to rehabilitate function, anatomical and aesthetic forms. Conclusion: Teeth that experienced rotation, crossbite, and avulsion due to trauma can be treated with multidisciplinary treatment through endo restoration and fixed-fixed bridge to rehabilitate stomatognathic function.